Antioxidants in Higher Plants - Alscher, Ruth G; Ed. Hess, John L; Ed (CRC PRESS, 1993)
Provides a blend of molecular and biochemical approaches to cover the state of the art in antioxidant function. The chemistry and protective potential of sulfhydyrl and hydroxyl compounds are emphasized. The significance of subcellular compartmentation is also discussed.